2017
DOI: 10.1080/23744235.2017.1407037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of measures to control brucellosis on disease characteristics in humans: experience from an endemic region in the Balkans

Abstract: The national strategy for brucellosis control, which included vaccination of small ruminants, resulted in a decrease of human brucellosis cases in the Republic of Macedonia and there was a tendency to milder disease manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Veterinarians and veterinary assistants showed to be largely exposed to Brucella spp., totalizing 189 individuals with positive diagnostic of brucellosis. Those infections, probably related to PLOS NEGLECTED TROPICAL DISEASES their occupational activities, were reported by fifteen articles [2,19,23,24,28,31,35,43,[50][51][52][53][54][55][56], mostly from Asia (n = 121), Europe (n = 40), and Americas (n = 27) and the minority from Africa (n = 1). Manipulation of live attenuated anti-brucellosis vaccines, described in seven studies, was the most reported exposure source (Table 3).…”
Section: Veterinarians and Veterinary Assistantsmentioning
confidence: 99%
“…Veterinarians and veterinary assistants showed to be largely exposed to Brucella spp., totalizing 189 individuals with positive diagnostic of brucellosis. Those infections, probably related to PLOS NEGLECTED TROPICAL DISEASES their occupational activities, were reported by fifteen articles [2,19,23,24,28,31,35,43,[50][51][52][53][54][55][56], mostly from Asia (n = 121), Europe (n = 40), and Americas (n = 27) and the minority from Africa (n = 1). Manipulation of live attenuated anti-brucellosis vaccines, described in seven studies, was the most reported exposure source (Table 3).…”
Section: Veterinarians and Veterinary Assistantsmentioning
confidence: 99%
“…The treatment that was administrated in our patient did not differ from the therapeutic approach used in patients with uncomplicated brucellosis in this region [2]. The treatment resulted with successful response rendering the thyroiditis in a shorter period than seen in several other studies [3,7,9,10].…”
Section: Discussionmentioning
confidence: 62%
“…It is one of the most widespread zoonoses worldwide. Brucellosis has high morbidity, both for humans and animals; It is an important cause of economic loss and a public health problem in many developing countries [2].…”
Section: Acute Thyroiditis Associated With Brucellosis: a Case Reportmentioning
confidence: 99%
“…Most people infected with brucellosis have an apparent history of exposure, such as exposure to infected animals, ingestion of brucella contaminated animal products, and inhalation of brucella containing aerosols. Brucellosis is able to cause various symptoms involving multiple systems [ 4 ] and easy to be misdiagnosed due to lack of specificity. Here, we report a male 5-year-and-11-month old Chinese child, who was diagnosed brucellosis with meningoencephalitis, coronary aneurysm and keratitis, which has not been reported before.…”
Section: Introductionmentioning
confidence: 99%